Montessori philosophy and its application in preschools - Escudero, Evelina Guevara (2005)
This study analyzed the Montessori philosophy of education, its core ideas and pedagogy and how this philosophy is faithfully applied in selected Montessori preschools in Metro Manila. Six Montessori preschools participated and was evaluated using the following criteria: the mission and vision of the school; the teachers; the prepared environment; the curriculum and classroom activities; and the student evaluation and assessment used in the school. The administrators and teachers believe that education develops the child when given freedom to choose his work in a prepared environment. Majority of parents feel likewise.
"October 2005."
Thesis (Ph.D.Education)--University of the Phillipines Diliman.
Keywords: Montessori method of education -- Philippines -- Manila Metropolitan Area; Education, Preschool -- Philippines -- Manila Metropolitan Area -- Activity programs